DETERMINANTS OF CAPITAL STRUCTURE IN CONSUMER NON-CYCLICALS COMPANIES LISTED ON IDX FOR 2021-2024 - Davin Edrick; Merry Susanti (International Journal of Application on Economics and Business, 2026)
This study seeks to examine the relationship between sales growth, liquidity, and firm size and the capital structure of consumer non-cyclical companies listed on the Indonesia Stock Exchange during the 2021 to 2024 period. The research background is rooted in the funding pressures that emerged after the COVID-19 pandemic, when rising raw material prices and higher interest rates simultaneously reduced corporate financial flexibility and increased borrowing costs for both operational and investment activities. These conditions created a dilemma for companies in this sector, as they were required to maintain business performance while facing limited funding capacity, making an assessment of internal factors influencing capital structure increasingly relevant. To obtain a more systematic empirical understanding, the study employs a quantitative approach with purposive sampling based on the availability of annual financial statements denominated in rupiah. Through this procedure, secondary data from 54 companies were collected, resulting in a total of 186 observations used for analysis. The findings show that sales growth has a positive effect on capital structure, indicating that expanding firms tend to increase their proportion of debt to support further growth. In contrast, liquidity exhibits a negative effect because greater internal funds allow firms to reduce dependence on external financing. Meanwhile, firm size does not show a significant effect, suggesting that the scale of assets is not a dominant factor in determining capital structure within the consumer non-cyclical sector during the observation period.